Characterization of thermally evaporated silver nanoparticles on graphene oxide coated substrate using hot-wire chemical vapour deposition / Nurul Hazierah Kamaruddin - Nurul Hazierah , Kamaruddin (2018)
In this research, silver nanoparticles (AgNPs) were grown by thermal evaporation technique in hydrogen gas ambient in a hot wire chemical vapour deposition (HWCVD) system. The graphene oxide (GO) thin films were spin coated onto either quartz or glass substrates in GO suspension synthesized by simplified Hummer’s method from graphite flakes. AgNPs were grown on both bare and GO coated substrates to study the effects of the GO films on the properties and antibacterial activities of the AgNPs. The influence of deposition time of silver wire and substrate temperature during the AgNPs growth and post annealing environment on the morphology, optical and structural properties of the AgNPs were investigated. The field emission scanning electron microscopy images showed that the shape of AgNPs on GO coated quartz substrates was tunable towards spherically shaped nanoparticles with variation in growth parameters and post-annealing environment. The average size of AgNPs increased with the increase of growth time and the yield of uniform nanoparticle distribution was obtained at higher substrate temperature. AgNPs post-annealed in nitrogen gas environment were smaller in size as compared the AgNPs post-annealed in vacuum. Embedding AgNPs into GO film matrix showed significant effects on its structure and optical properties. Surface enhanced Raman scattering effect was obvious when AgNPs were introduced into the GO matrix. The size distribution and homogeneity of the AgNPs were consistent with the surface plasma resonance behavior of the AgNPs. Quenching of the photoluminescence intensity of AgNPs on GO coated substrate demonstrated a decrease in the electron-hole recombination rate. Electrical measurements on AgNPs on GO coated quartz substrates used in organic photovoltaic solar cell device structure showed four-fold enhancement in current density (JSC) as compared to conventional organic solar cells without AgNPs. The antibacterial activity of AgNPs on GO coated glass substrates tested on Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) showed an increase in the area of zone of inhibition for bacteria as compared to AgNPs on bare glass substrates.